KAJIAN LITERATUR DAN PELUANG RISET PENERAPAN CLAWBACK PROVISIONS DI INDONESIA - Ida Ayu Purnama (AKUNTANSI DEWANTARA, 2021)
The purpose of this study is to provide a broad overview of the clawback provision and research ideas related to the implementation of clawback in Indonesia. In addition, there is also a research on the good and bad impacts of the implementation of clawback in Indonesia. The application of clawback can have a good impact on Indonesia in terms of improving company performance, increasing public and investor confidence, but it is also necessary to consider the different cultural factors between Indonesia and America that cause the impact of implementing clawback cannot produce the same result.